EFFECTIVENESS OF THE USE OF L-CARNITINE FOR THE CORRECTION OF METABOLIC DISORDERS IN CHILDREN OPERATED FOR CONGENITAL COLORECTAL PATHOLOGY - V.О. Fofanov; О.D. Fofanov; А.B. Volosyanko; А.P. Yurtseva; І.М. Diduh (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2023)
The relevance of the problem of congenital colorectal pathology (CCP) in children, which includes Hirschsprung's disease (HD) and anorectal malformations (ARM), is due to a significant number of early and long-term postoperative complications that may require long-term treatment and repeated reconstructive operations. This issue has an important medical and social significance, which is connected, first of all, with a significant spread of HD and ARM, frequent combination with other defects, a pronounced long-term deterioration of the quality of life of sick children. In the case of abdominal surgical pathology, in particular, in the case of CCP, due to surgical trauma and perioperative nutrient deficiency, the probability of developing metabolic disorders and energy deficiency is quite high. Taking into account the detoxification, antihypoxic and antioxidant effects of L-carnitine, an L-carnitine-containing drug was prescribed to correct the identified metabolic disorders and energy deficiency. In conditions of insufficient nutrition in children with CCP caused by the underlying disease, L-carnitine deficiency in children with this pathology is quite possible. Data from fundamental research in recent years have shown that the correction of metabolic disorders and energy protection is a progressive direction to which the future belongs. The purpose of the study is to evaluate the effect of the use of L-carnitine-containing drug on the clinical course of the postoperative period and indicators of the redox system of glutathione and metabolites of energy metabolism in children with CCP. The study included 57 patients with CCP, divided into two groups: the main group - 30 children with CCP, who in the postoperative period received basic rehabilitation therapy and the L-carnitine-containing drug Agvantar; the comparison group – 27 patients who received only symptomatic and basic rehabilitation therapy. The control group included 20 children of the same age who did not suffer from infectious and inflammatory diseases during the last 2 months. In both groups of patients, the study evaluated the parameters of the glutathione redox system and metabolites of energy metabolism in dynamics 1 month after surgery. Under the influence of the use of the L-carnitine-containing drug, positive dynamics of the clinical course of the postoperative period were established, a tendency to normalize the content of antioxidant enzymes of the glutathione redox system and indicators of energy metabolism was noted, which testifies to its effectiveness. Its effectiveness is proven, and the feasibility of its appointment in the postoperative period in children with HD and ARM has been established.